Impact of a "No Mobile Device" Policy on Developmental Surveillance in a Pediatric Clinic. (September 2018) - Regan, Paul A.; Fogel, Benjamin N.; Hicks, Steven D.
Children commonly use mobile devices at pediatric office visits. This practice may affect patient-provider interaction and undermine accuracy of developmental surveillance. A randomized, provider-blinded, controlled trial examined whether a policy prohibiting mobile device use in a pediatric clinic improved accuracy of pediatricians' developmental surveillance. Children, aged 18 to 36 months, were randomized to device-prohibited (intervention; n = 58) or device-allowed (control; n = 54) groups. After a 30-minute well-visit, development was evaluated as "normal, " "borderline, " or "delayed" in 5 categories using the Ages and Stages Questionnaire (ASQ-3). ASQ-3 results were compared with providers' clinical assessment in each category. Provider-ASQ discrepancies were more common for intervention participants ( P = .025). Providers "missed" more ASQ-3 "delayed" scores ( P = .005) in the intervention group, particularly in the fine motor domain ( P = .018). Prohibiting mobile device use at well-visits did not improve accuracy of providers' developmental surveillance. Mobile devices may entertain children at well-visits, allowing opportunities for parent-provider discussion, or observation of fine motor skills.